Chiral-selective growth of single-walled carbon nanotubes on Fe-based catalysts using CO as carbon source. (November 2016) - He, Maoshuai; Fedotov, Pavel V.; Chernov, Alexander; Obraztsova, Elena D.; Jiang, Hua; Wei, Na; Cui, Hongzhi; Sainio, Jani; Zhang, Weiguo; Jin, Hua; Karppinen, Maarit; Kauppinen, Esko I.; et al.
Abstract: MgO supported monometallic Fe (FeMgO) and bimetallic FeMn (FeMnMgO) catalysts were developed for growing carbon nanotubes using CO as carbon source. Characterizations on the FeMgO catalyst revealed that Fe cations were well-dispersed in the porous MgO support, forming a solid solution. Since most Fe cations in the solid solution are difficult to reduce, FeMgO can only catalyze the growth of single-walled carbon nanotubes (SWCNTs) at temperatures of 700 °C and above. While Fe cations in FeMnMgO could be reduced at lower temperatures with the assistance of Mn, catalyzing the subsequent growth of SWCNTs. Compared with most SWCNTs grown on components like Co or Ni at ambient reaction pressure, the Fe-catalyzed SWCNTs demonstrate rather narrow chirality distributions. Particularly, preferential (6, 5) tube growth on FeMnMgO was achieved at 600 °C. The narrow SWCNT chirality distribution could be inherently related to the high carbon solubility of Fe nanoparticles, favoring the nucleation of SWCNTs by a perpendicular mode. The present studies not only offer essential insights into SWCNT growth mechanisms, but can guide the design of novel catalysts for chirality-controlled growth of SWCNTs.